Perancangan Inverter Satu Fasa 12V DC KE 220V AC Berbasis IC TIMER NE555 - Angga Hermawan; Andre Jonatan Tambunan; Triniti Stefany; Sofian Parhusip (GLOBAL SCIENTS PUBLISHER, 2026)
An inverter is an electronic device that functions to convert direct current (DC) into alternating current (AC). In this design, a single-phase inverter is created that is capable of converting 12V DC voltage to 220V AC by utilizing the NE555 timer IC as a square wave signal generator in astable mode. The frequency is set using a resistor, potentiometer, and capacitor. The output signal is then amplified by the S8050 transistor and used to control two IRFZ44 MOSFETs as switching switches on the center tap transformer. The transformer functions to increase the voltage up to 220V AC. This circuit uses supporting components such as resistors and capacitors to maintain work stability. Test results show that the inverter is capable of producing AC voltage with a frequency close to 50 Hz in the form of a square wave, making it suitable for use with simple loads such as lamps and low-power electronic devices.